Budgetary deficits and macro budgetary components- examining ‘Law of Contiguity’ through spatial analysis of Indian states - Avik Ghosh (Development Studies Research, 2025)
Spatial economics deals with the mutual socioeconomic influence of the geographical boundary of an administrative body on the neighboring entities- municipalities, districts, states, and countries. Researchers have conducted spatial analyses to solve a variety of economic problems like labor dynamics, wage equilibrium, capital formation, and demographic agglomeration/dispersion, among others. However, the application of spatial economics in public finance, despite being a pressing priority, has not been extensively explored. With India being the largest democracy in the world and having a decentralized state budget mechanism in place, focused attention is required to measure the contiguity effect in state finance. I find strong spatial dependence by implementing a fixed effect panel regression design followed by a spatial regression approach to assess fiscal health in Indian states over 22 years. The analysis reveals spatial dependence on both the income and expenditure sides of state budgetary fiscal and primary deficits. I also analyze the dynamics of the capital budget revenue and its idiosyncrasies in determining the spatial roles that govern state deficits. The empirical results underscore that fiscal policymaking through budget preparation for an Indian state must account for major fiscal components of bordering states to achieve targeted fiscal objectives.